Patient-Reported Outcome Measures for Breast Implant Surgery: A Pilot Study. (3rd February 2019) - Ng, Sze; Pusic, Andrea; Parker, Emily; Vishwanath, Swarna; Cooter, Rodney D; Elder, Elisabeth; Moore, Colin; McNeil, John; Hopper, Ingrid
Abstract: Background: The Breast-Q Implant Surveillance module (BREAST-Q IS) is a patient-reported outcome measure (PROM) that asks 5 questions on satisfaction (shape, feel, and rippling) and symptoms (pain and tightness) derived from the BREAST-Q. Objectives: We aimed to pilot BREAST-Q IS on patients within the Australian Breast Device Registry (ABDR), an opt-out clinical quality device registry, and explored Short Message Service (SMS) communication as a follow-up method. Methods: Patients with a breast device surgery in the previous 10 to 15 months, age ≥18 years, with a mobile phone number, were invited to complete the 5-question PROM via SMS initially, followed by 3 phone call attempts if no response, an e-mail, and then a letter by post as a final engagement strategy. Results: The study included 197 participants [breast augmentation (BA) = 118; breast reconstruction (BR) = 79]. Mean ± SD age was 40 ± 12 years (BA) and 44 ± 11 years (BR). Mean ± SD time since surgery was 414 ± 36 days (BA) and 413 ± 51 days (BR). The total response rate, including opt-outs, was 76%. Responses indicated that >90% of BA and >79% of BR were very or somewhat satisfied with shape, feel, and wrinkling; >70% of BA and >46% of BR reported no pain or tightness. Completion of survey via SMS was 51% (BA) and 55% (BR). Further responses were received by phone (25%, 26%), post (21%, 16%), and e-mail (3%, 3%). Conclusions: This pilot demonstrated high levels of satisfaction and low levels of pain and tightness in patients with breast augmentation and breast reconstruction 1 year postoperatively. It also showed the effectiveness of our engagement strategy, which achieved a 76% response rate. Over 50% of respondents used SMS to reply to a 5-question PROM assessing long-term surgical outcomes. This engagement strategy will be used as BREAST-Q IS is rolled out nationally.